Clinical outcomes of polymeric sealant use in pulmonary resection: a systematic review and meta-analysis of randomized controlled trials - McGuire, Anna L.; Yee, John (Journal of Thoracic Disease, 2018)
Background: Prolonged alveolar air leak (PAL) is the most common adverse event following pulmonary resection. It carries morbidity for patients by increasing empyema risk, and for hospital administration with the cost of prolonged length of hospital stay (LOS). Intra-operative sealant technology is available to surgeons, and may decrease PAL. Our aim was to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) on the effect of intraoperative polymeric sealant use on PAL, empyema, and LOS. Methods: Standard PRISMA (Preferred Reporting Items for Systematic reviews and Meta-analysis and methods) protocol was adhered to. For qualitative review the search strategy yielded 21 RCTs reporting polymeric sealant use in lung resection, 19 of which were included in meta-analyses. The control arm in the two excluded RCTs was not “standard care.” Random-effects meta-analyses were conducted. Inter-trial heterogeneity was assessed with the I2 statistic. Publication bias was assessed with a funnel plot and Egger statistic for small study effects. Results: Pooled analysis was derived from 2,537 randomized participants. They were allocated to the intervention arm of lung resection with intra-operative application of a polymeric sealant (n=1,292), or the control arm of standard care involving pulmonary resection with pneumostasis by sutures and/or stapler (n=1,245). Participants came from 10 different countries, with mean (SD) age of 62.5 (4.2) years, and 31.6% (95% CI: 30.0–33.5) female. Pooled estimates revealed polymeric sealant decreased odds of PAL (OR 0.55, 95% CI: 0.35–0.87), and decreased LOS by one day (mean difference −0.96, 95% CI: −1.74 to −0.18), without increasing odds of pleural sepsis (OR 1.134, 95% CI: 0.343–3.748). There was evidence of publication bias in the LOS meta-analysis. Conclusions: Pooled analysis revealed decreased odds of PAL, and decreased LOS by one day with intraoperative use of polymeric sealants. There was no associated increase in odds of adverse events, including empyema.